O sommelier de vinhos no mercado enogastronômico de São Paulo: hospitalidade e prática - DUARTE, Renato Luis da Rocha (2016)
This study sought analyze the elements that characterize the sommelier profession of wines and their performance in enogastronomia São Paulo, based on the services sector in hospitality. As search criteria, it was approached the evolutionary aspects of wine. It was also Analyzed the wine sommelier profession of, its genesis, evolution, functions and perspectives for the future of the profession. In this respect it was showen up the enogastronomia concepts in Sao Paulo and also have been addressed, the dimensions of hospitality in providing services in enogastronomy. The main aim of this study was to investigate whether the hospitality services applied in providing sommelier services add value to the sommelier, the establishment and the increased frequency and customer loyalty, thus generating a virtuous commercial circle. It was also used as a source of study and research, concrete data obtained through fieldwork, with visitation and data collection for further proof of the reality of the wine sommelier's work as well as their participation in enogastronomic job market in Sao Paulo. The results of this study proves that hospitality services applied in enogastronomia add value and benefits to professionals who practice them.